Dissolved Oxygen in Heterogeneous Environments Dictates the Metabolic Rate and Thermal Sensitivity of a Tropical Aquatic Crab - Fusi, Marco; Daffonchio, Daniele; Booth, Jenny; Giomi, Folco (Frontiers in Marine Science, 2021)
Oxygen availability, together with water temperature, greatly varies in coastal habitats, especially in those characterized by elevated primary production. In this study, we investigate the combined role of dissolved oxygen and temperature on the thermal physiological response of the mud crab Thalamita crenata living in an equatorial system of coastal habitats. We sampled temperature, oxygen and salinity in T. crenata habitats, mangrove creeks and fringes and seagrass meadows, at Gazi Bay (Kenya). We found that seagrass meadows exhibited higher temperature and oxygen saturation than the mangrove habitats during the day, creating conditions of oxygen supersaturation. By investigating the effect of different levels of oxygen saturation on the thermal response of T. crenata, we demonstrated that the respiratory physiology of this ectotherm has a pronounced resistance to heat, directly influenced by the amount of dissolved oxygen in the water. Under low oxygen saturation levels, the mud crab significantly reduced its metabolism, becoming temperature-independent. This result shows that aquatic species can modulate their thermal response in a stringent dependency with water oxygen saturation, corroborating previous findings on the thermal response of T. crenata under supersaturation. This contribution provides further support for the need to adopt an ecologically-relevant approach to forecast the effect of climate change on marine ectothermal species.